"Ice" Beneath the Deep Sea: Studies of Methane Hydrate Layers Beneath the Continental Slope off Vancouver Island - Hyndman, R. (Geoscience Canada, 1992)
Summary Deep-sea methane hydrate "ice" layers are found a few hundred metres beneath the continental slopes of a number of areas around the world, notably in subductionzones where large accretionary sedimentary prisms are formed. The ice-like clathratestructure is stable up to temperatures of 10°-30°C beneath the sea floor at the pressures generated by water depths greater than about 800 m. The primary indicator of deep-sea hydrate is a "bottom simulating reflector'' (BSR) that parallels the sea floor. These naturally occurring hydrate layers are estimated to contain a very large amount of methane, a potential clean fuel resource, butit is unlikely that recovery will be possible in the near future. Of more immediate concern is the role of such hydrate in global climate control. Because methane is a very strong greenhouse gas, release to the atmosphere of methane in hydrate resulting from a small amount of climatic warming could strongly enhance the warming trend, i.e., provide positive feedback. Recent results, especially from the Vancouver Island margin, are summarized, dealing with a) the distribution and amount of such hydrate, b) the nature of the hydrate layers revealed by detailed seismic reflection analysis, and c) the hydrate formation process. A hydrate BSR is found to be widespread in a 30 km wide band beneath much of the continental slope off Vancouver Island. The hydrate layer in this area is on the order of 20 m thick, concentrated at the baseof the stability field about 300 m below the sea floor. Because such deep-sea hydratere presents a very large global methane reservoir, its distribution, nature and formation warrant detailed study.